Bloodstream infections at a tertiary hospital in the Gambia - a one-year retrospective study - Paul Rahden; Ebrima Barrow; Haddy Bah; Sheikh Omar Bittaye; David Nygren; Abdoulie Badjan (BMC Infectious Diseases)
Abstract Introduction Antimicrobial resistance is a significant global health concern, particularly in western Sub-Saharan Africa. This study describes causes of bloodstream infections and antimicrobial resistance at a tertiary hospital in The Gambia. Methods This retrospective analysis included all blood cultures performed at the Edward Francis Small Teaching Hospital, Banjul, The Gambia, from September 2022 to August 2023. Blood culture positivity-rates and pathogens were described. Antimicrobial susceptibility testing was performed using disk diffusion following the Clinical & Laboratory Standards Institute guidelines. Results A total of 645 patients had blood cultures drawn during the study period with 260 (40%) positive results. Contaminants were identified in 28 cases (4%). The majority were drawn from neonatal or paediatric patients (360/645, 56%) and overall primarily in intensive care units (406/645, 63%). The median age was 3 years (interquartile range 0–31 years) and 46% were female. The most common pathogens were Staphylococcus aureus 106/260 (41%), Klebsiella spp. 41/260 (16%), other bacteria within the Enterobacterales order 33/260 (13%), Pseudomonas spp. 22/260 (8%) and Acinetobacter spp. 19/260 (7%). Methicillin-resistant S. aureus (MRSA) was seen in 34/58 (59%) tested. Extended-spectrum beta-lactamases (ESBL) were seen in 36/40 (90%) of Klebsiella spp. and in 16/28 (57%) of other bacteria within the Enterobacterales order. Acquired antibiotic resistance, beyond wild-type, was reported in 17/20 (85%) of Pseudomonas spp. and 16/19 (84%) of Acinetobacter spp. Conclusion Overall, blood culture positivity rates were high, indicating restrictive testing suggesting that sample collection were restricted to mainly critically ill, neonatal or paediatric patients. Nonetheless, our data suggests a high proportion of bloodstream infections due to multi-drug resistant pathogens, including MRSA and ESBL-Enterobacterales. Importantly, generalisability of findings beyond this tertiary hospital setting remains restricted. However, our findings demonstrate a need for improved diagnostic stewardship and ongoing surveillance to provide robust evidence-based data to inform antimicrobial resistance interventions.